APPLICABILITY OF LDL-CHOLESTEROL CALCULATION FORMULAS IN HYPERTRIGLYCERIDEMIA: INSIGHTS FROM THE VOJVODINA: LDL-C FORMULAS IN HYPERTRIGLYCERIDEMIA - Žuvić, Dragana; Nikolić, Stanislava; Mijović, Romana; Ilinčić, Branislava; Ranđelović Živković, Aneta; Sedlarević, Dušan; Čabarkapa, Velibor (Journal of Medical Biochemistry, 2026)
Background: LDL-cholesterol is a key parameter for assessing the risk of atherosclerotic cardiovascular disease. Direct measurement of LDL-cholesterol is not always possible due to practical or financial reasons, making the use of calculation formulas essential for its evaluation. The aim of this study was to examine the applicability of four different formulas for calculating LDL-cholesterol compared to direct method in patients with serum triglyceride levels from 4.5 to 9.0 mmol/L in the population of Vojvodina.Methods: The retrospective study included 272 subjects whose lipid status parameters were measured using standard laboratory methods between June 2022 and June 2023. The participants had serum triglyceride levels ranging from 4.5 and 9.0 mmol/L. LDL-cholesterol was determined by direct method (d-LDL-C) on Alinity c analyser (Abbott). Additionally, LDL-cholesterol levels were calculated for this population using the formulas proposed by Friedewald, Sampson, Anandaraja and Martin.Results: In the studied population, the average age was 52 years and the median concentration of triglycerides was 5.48 (4.94-6.58) mmol/L. A statistically significant positive correlation was found between d-LDL-C and all calculated parameters (P
Keywords: lipids; cholesterol, LDL; hypertriglyceridemia; Sampson formula